Characteristics of a newly diagnosed Polish cohort of patients with neurological manifestations of Wilson disease evaluated with the Unified Wilson’s Disease Rating Scale - Członkowska, Anna (BMC Neurol, 2018)
BACKGROUND: Wilson disease is a rare genetic disorder in which impaired copper excretion results in toxic copper levels and tissue damage. Manifestations are primarily hepatic and/or neuropsychiatric, with a variety of neurological phenotypes. The aim of this study was to characterize neurological signs of Wilson disease in newly diagnosed patients and to determine whether they correlated with disability, liver function, and copper metabolism. METHODS: Fifty-three treatment-naïve patients recently diagnosed with Wilson disease who exhibited neurological symptoms were included. Neurological manifestations were characterized by examination in terms of symptom type and degree of neurological impairment (Unified Wilson’s Disease Rating Scale [UWDRS] Part III) and correlated with degree of disability (UWDRS Part II), abnormalities in copper parameters and hepatic status. RESULTS: Most patients (62.3%) exhibited tremor and ataxia, whereas 15.1% were dystonic, and 11.3% had parkinsonism. Discrete or unclassified signs only were observed in 11.3% of patients. A good correlation between disability (UWDRS Part II) and neurological impairment (UWDRS Part III) was observed (Pearson r = 0.84). However, there was a lack of correlation when either disability or neurological impairment were analyzed with copper parameters or liver impairment. CONCLUSIONS: The predominant neurological manifestations in this cohort of newly diagnosed Wilson disease patients were ataxia and tremor. Neurological impairment measured was highly correlated with the level of disability. However, hepatic manifestations of Wilson disease and copper levels did not appear to be correlated with neurological status and disability. These results highlight the challenges faced when assessing Wilson disease with its highly variable symptomatology. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12883-018-1039-y) contains supplementary material, which is available to authorized users.